Effects of high pressure and thermal processing on phytochemical, color and microbiological qualities of herbal-plant infusion - Chaikham P. (2014)
The objective of the present study was the evaluation of the bioactive compounds, physical properties and microbiological qualities of herbal-plant infusion as affected by high pressure processing (400 or 500 MPa at 25°C for 15 or 30 min) and thermal processing (90°C for 1-3 min). It was found that pressurized infusions comprised of high concentrations of gallic acid, ellagic acid, total polyphenols, ascorbic acid, asiatic acid and gamma oryzanol compared to the pasteurized samples. Color parameters displayed that pressurization could conserve the natural color of the products better than pasteurization. The microbiological assessments showed that total plate counts, yeasts-moulds and fecal coliforms in both processed infusions were acceptably eliminated. © All Rights Reserved.